2019
DOI: 10.13189/ujmr.2019.070101
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of Lipase Enzyme Expressed by Crude Oil Contaminated Soil Isolates

Abstract: Lipases are hydrolytic enzymes responsible for the hydrolysis of triacylglycerol into glycerol and free fatty acids. The biodiversity of crude oil contaminated soil was explored for the isolation of novel potent lipase producing microorganisms. In this current study, microorganisms isolated from crude oil contaminated soils were screened for lipase activity and expression. Six fungal strains namely: Yeast, Aspergillus flavus, Aspergillus niger, Verticillus sp., Penicillum sp., and Microsporum audouini demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Among the fungi isolated in this study, Penicillium notatum was prominent across all plots sampled. Elemuo et al [25] have reported the versatility of P. notatum in the environment with ability to produce various enzymes, which helped the microorganisms degrade crude oil in contaminated environment.…”
Section: Discussionmentioning
confidence: 99%
“…Among the fungi isolated in this study, Penicillium notatum was prominent across all plots sampled. Elemuo et al [25] have reported the versatility of P. notatum in the environment with ability to produce various enzymes, which helped the microorganisms degrade crude oil in contaminated environment.…”
Section: Discussionmentioning
confidence: 99%
“…The samples collected were centrifuged at 3000 rpm for 10min before using it for enzyme assay analysis [2,15]. Three enzyme solutions belonging to the classes of lipases and amylase investigated in this study are both isolates of fungi [ 15 ], and it is been presented in Table 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Such hydrolytic enzymes are important for C, N, and P acquisitions and are therefore meaningful indicators for soil functions [ 25 , 26 ]. Lipases are hydrolytic enzymes produced by animals, plants, and microorganisms, which are responsible for the hydrolysis of triacylglycerol into glycerol and free fatty acids [ 27 , 28 ]. Lipases therefore mediate degradation processes of many BBPs [ 10 , 29 ].…”
Section: Introductionmentioning
confidence: 99%